2015
DOI: 10.14214/sf.1266
|View full text |Cite
|
Sign up to set email alerts
|

Using thermal time models to predict germination of five provenances of silver birch (<i>Betula pendula</i> Roth) in southern England

Abstract: Using thermal time models to predict germination of five provenances of silver birch (Betula pendula Roth) in southern England Midmore E. K., McCartan S. A., Jinks R. L., Cahalan C. M. (2015). Using thermal time models to predict germination of five provenances of silver birch (Betula pendula Roth) in southern England. Silva Fennica vol. 49 no. 2 article id 1266. 12 p. Highlights• Using cumulative germination data, thermal time models were developed for Betula pendula.• Models indicated varying degrees of dorm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 33 publications
2
12
1
Order By: Relevance
“…Differences in germination rates among populations of B. pendula have been previously reported, even at smaller geographical scales ( Holm 1994a ). Similar to our results, Midmore et al (2015) predicted markedly high differences in germination rates among populations, ranging between 0 and 100 % among populations from 47°N to 60°N. Similar patterns of population-level variation have been found in other Betula species (e.g.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Differences in germination rates among populations of B. pendula have been previously reported, even at smaller geographical scales ( Holm 1994a ). Similar to our results, Midmore et al (2015) predicted markedly high differences in germination rates among populations, ranging between 0 and 100 % among populations from 47°N to 60°N. Similar patterns of population-level variation have been found in other Betula species (e.g.…”
Section: Discussionsupporting
confidence: 91%
“…S1 ] . Midmore et al (2015) showed that, on average, southern populations had a higher percentage of empty seeds (~77 %) than northern populations (~28 %). Southern B. pendula populations are generally more isolated, have smaller size, lower density and lower levels of genetic variation, which could have limited ovule fertilization rates because of more irregular pollen availability and/or inbreeding depression ( Holm 1994a ; Palmé et al 2003 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations